Private property as the main factor of building a modern society: key features, properties and theoretical approaches - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article describes the key features of private property, whose central concept is the principle of the inviolability of private property and state interference in the process of market exchange. We study the basic theoretical approaches to the private property. In addition, the article analyzes the state's role in forming the existing social structure and ownership and the main legal and economic prerequisite for the development of society.